Prevalence of Self-Neglect across Gender, Race, and Socioeconomic Status: Findings from the Chicago Health and Aging Project - Dong, XinQi (S. Karger AG, 2012)
BACKGROUND: Self-neglect is the behavior of an elderly person that threatens his/her own health and safety, and it is associated with increased morbidity and mortality. However, the scope of the self-neglect in the community population remains unclear. We examined the prevalence of self-neglect and its specific behaviors of hoarding, hygiene and other environmental hazards in a community-dwelling elderly population. METHODS: A population-based cohort study conducted from 2007 to 2010 in a single cycle in a geographically defined community of 4 adjacent neighborhoods in Chicago, Ill., USA. Participant's personal and home environment was rated on hoarding, personal hygiene, house in need of repair, unsanitary conditions, and inadequate utility. Prevalence estimates were presented across gender, race/ethnicity, education and income levels. RESULTS: There were 4,627 older adults in the cohort. The prevalence of self-neglect and specific personal and environmental hazards varied significantly by race/ethnicity and by levels of education and income. For race/ethnicity, black older adults (men 13.2%; women 10.9%) had a significantly higher prevalence of self-neglect than white older adults (men 2.4%; women 2.6%). For those with less than high school education, the prevalence of the self-neglect was 14.7% in men and 10.9% in women. For those with an annual income of less than USD 15,000, the prevalence of self-neglect was 21.7% in men and 15.3% in women. CONCLUSION: The prevalence of self-neglect and specific behaviors of hoarding, poor hygiene, and other environmental hazards are higher among black older adults and among those with lower levels of education and income.